Odpowiedzi

2010-02-28T17:29:50+01:00
A) 2(a +1) - 3(a - 5) = 7a a = 2
2a+2-3a+15=7a
2*2 + 2 - 3*2 + 15 = 7*2
4+2-6+15 = 14
15 ≠ 14
L ≠ P

b) 3x(x - 5) = (x-2)(3x-3) x= -1
3x²-15x = 3x²-3x-6x+6
3*(-1)² - 15*(-1) = 3*(-1)² - 3*(-1)- 6*(-1) + 6
3*1 + 15 = 3*1 + 3 + 6 + 6
3+15 = 3+3+6+6
18=18
L=P

c)3/5x - (7/9x-¼) = 2-(x+3)/4 x=O
3/5*0 - 7/9x+¼ = 2-x-3 / 4
0-0+¼ = 2-0-3 / 4
¼ = 2-3 / 4
¼=-¼
L≠P
4 3 4
Najlepsza Odpowiedź!
2010-02-28T17:31:41+01:00
A)2(a+1)-3(a-5)=7a
2(2+1)-3(2-5)=7*2
6+9=14
15=14 nie spelnia

b)3x(x-5)=(x-2)(3x-3)
-3(-1-5)=(-1-2)(-3-3)
3+15=-3*(-6)
18=18 spelnia

c)3/5x-(7/9x -¼)=2-(x+3)/4
¼=2-3 /4
¼=¼


3 2 3